Psychological assessment of stress-coping styles and the personality traits students of the Medical University of Gdańsk - Żuralska, Regina; Majkowicz, Mikołaj; Gaworska-Krzemińska, Aleksandra (Nursing Problems / Problemy Pielęgniarstwa, 2012)
Introduction. Occupation of nurse and midwife requires mastery of relevant knowledgeand coping skills and the formation of such personality traits which will be an essential condition for the exercise vocational tasks which are considered socially. Aim of the study. The aim of research was to analyze the relationship between styles of coping with stressful situations and the level of personality traits included in the three-factor model of Eysenck’s personality in nurses and midwives. Material and methods. The study included 220 students, including 114 students of nursing,an average age of 36.29 years (SD = 9.54) and 106 midwifery students, with an average age of 36.48 years (SD = 7.77), Medical University of Gdansk. Research was conducted using the Eysenck EPQ R and CISS Endler and Parker. Results and conclusions. Analysis of own research showed that nursing students often than female students preferred the style of midwifery focused on the task and searching for social contact. It was found in both groups many statistically significant relationships between styles of coping and personality. Specified action is to improve awareness of of nurses and midwives on their own resources and limitations, and implementation of systematic training in social skills.